Analisis Perubahan Rasio Keuangan Dalam Menilai Kinerja Keuangan Terhadap PT Astra Agro Lestari Tbk Tahun 2022 Dan 2023 - Furkan (JURNAL ECONOMINA, 2024)
Financial reports are a form of company description. With this financial report you can see how the company's financial performance is. Financial performance is defined as something that is really needed by the company, both internally and externally. This research uses a quantitative type of research. This research focuses on looking at the company's financial performance through activity ratios, solvency, liquidity and profitability. The research focuses on PT Astra Agro Lestari Tbk in 2022 and 2023. The data collection method used is through literature study from journals, scientific articles and other sources. Data analysis uses descriptive analysis from the results of ratio calculations. The results of this research show that calculations of liquidity ratios, activity ratios and profitability obtain results that can be said to be still bad for PT companies. Astra Agro Lestari Tbk, while the solvency ratio results obtained good results at PT. Astra Agro Lestari Tbk.